2023
DOI: 10.1021/acsomega.3c04121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prestirring Time on Carbon Removal from Coal Fly Ash in the Flotation Technology

Abstract: Coal fly ash (CFA) is one of the industrial byproducts of burning coal for energy production and has unburned carbon, which negatively affects its full potential use. The flotation technology can be effective in separating unburned carbon from CFA, and the prestirring time is crucial for the ideal initial conditions during the flotation process. To find the suitable prestirring time, eight prestirring times, including 0, 1, 2, 3, 4, 5, 6, and 7 min, were selected in this paper, followed by flotation of CFA aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…These results are consistent with the previously reported literature studies on coal ashes [32][33][34]. Although the presence of C atoms in coal ashes might be due to the residual carbonaceous materials, the low amounts of C atoms might be attributed to the excess oxidation condition in the steam boiler [35]. Considering the high atomic percentage of O atoms, it might be suggested that both ashes are composed of SiO 2 , Al 2 O 3 , and Fe 2 O 3 , which are well-known electroactive materials [36,37].…”
Section: Characterizations Of Cfa and Cbasupporting
confidence: 93%
“…These results are consistent with the previously reported literature studies on coal ashes [32][33][34]. Although the presence of C atoms in coal ashes might be due to the residual carbonaceous materials, the low amounts of C atoms might be attributed to the excess oxidation condition in the steam boiler [35]. Considering the high atomic percentage of O atoms, it might be suggested that both ashes are composed of SiO 2 , Al 2 O 3 , and Fe 2 O 3 , which are well-known electroactive materials [36,37].…”
Section: Characterizations Of Cfa and Cbasupporting
confidence: 93%